PENTINGNYA MAHASISWA PRODI KEWIRAUSAHAAN UNIVERSITAS MEGAREZKY MAKASSAR DALAM MEMAHAMI PERILAKU ORGANISASI BISNIS - Bine, Enjelin; Jannah, Mifta; Madai, Hengky (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2024)
This research was conducted with the aim of analyze and exploring the extent to which entrepreneurship study program students understand the importance of studying organizational behavior and how students can apply their understanding in the future to the importance of understanding organizational behavior in the future. The method used in this research is a qualitative method. The results of this research confirm the importance of students understance and studyng organizational behavior. Organizational behavior is a behavior or way of someone in an organizational group. In a business, organizational behavior is very necessary, because establishing relationships within an organization, both between individuals and groups, requires behavior. In a company or organization, one important aspect that must be considered is organizational behavior, where a company must know every behavior or characteristic between individuals and groups within the organization.